Accuracy of Handheld Continuous - Wave Doppler Ultrasound in the Assessment of Varicose Veins. - Siow, LR; Naresh G,; Kosai NR,; Harunarashid H,; Sutton PA,; Zainal AA, (Faculty of Medicine, UKM Medical Centre, 2015)
The incidence of varicose veins and the need for treatment has shown a tremendous increase over the years.Debilitating venous ulcers and dragging edemas of the lower limb with overall improvement in cosmetic results and availability of endovenous procedures has brought many patients forward for treatment. Continuous-wave handheld Doppler usage is imited by its diagnostic capabilities, thus the need to determine its real effectiveness. Benefits of using hand-held dopplers lies in its rapidity in assessment of patients, it's low running cost and short learning curve. This is important as duplex ultrasounds are not readily available in district hospitals. This study aims to determine the clinical effectiveness of hand-held continuous wave opplers in the local setting especially in primary uncomplicated aricose articles veins. All electively referred patients with primary uncomplicated varicose veins who were referred to the Varicose Vein Clinic were evaluated with continuous-wave handheld Doppler (CWD) and duplex ultrasound (DUS) examination. The study duration was from the 1st of July to 31st of August 2013 (2 months). All patients in the study were independently evaluated with CWD and DUS in the clinic on the same day after adequate rest time. DUS was taken as the gold standard for evaluation of CWD specificity and sensitivity. The Chi-square and T-test was used to test for statistical significance. A total of 41 patients were valuated in this study. The specificity of CWD when ompared to DUS for diagnosing Sapheno-femoral junction (SFJ) was 100% and at the Sapheno-popliteal junction (SPJ) was 87%. Meanwhile sensitivity of CWD for SFJ was 75% and SPJ was 0%. The examination time with CWD was significantly faster than when compared with DUS examination with significant faster tracing times that can be achieved with CWD. CWD also significantly shorter reflux times when compared to DUS. Continuous-wave handheld doppler proves to be an ndispensable clinical tool in the evaluation of SFJ and SPJ reflux in varicose veins. CWD assessment in this study was shown to be equal if not better for evaluating reflux when compared to DUS assessment for SFJ reflux. Main advantages for CWD also lie in its low running cost, rapidity in assessment and short learning curve when compared to duplex ultrasound examinations.